The Influence of Socio-Philosophical Processes in the 9th–10th Centuries on The Scientific-Philosophical Views of Abu Nasr Farabi - Kenjaeva Dilrabo Rominovna; Khaidarova Larisa Sunnatovna (Scientific Trends, 2025)
This article analyzes the socio-philosophical processes in Central Asia and the Middle East in the 9th–10th centuries and reveals their influence on the worldview and scientific and philosophical views of the great thinker Abu Nasr al-Farabi. The interrelationships between science, philosophy, politics, and religion during the time of al-Farabi, as well as the Arabization of Greek philosophy, were important factors in the formation of al-Farabi's views.
Keywords: Al-Farabi, philosophy, 9th–10th centuries, social thought, Greek philosophy, Islamic revival, development of science.